Effect of amylolysis on the formation, the molecular, crystalline and thermal characteristics and the digestibility of retrograded starches - Villas-Boas, Flávia [UNESP]; Facchinatto, William Marcondes; Colnago, Luiz Alberto; Volanti, Diogo Paschoalini [UNESP]; Franco, Celia Maria Landi [UNESP] (Elsevier, 2020)
This study evaluated the effect of amylases on the formation, and characteristics of retrograded starches using sweet potato (SPS), cassava (CAS) and high amylose maize (HAS) starches. The starches were gelatinized, hydrolyzed with fungal or maltogenic α-amylase, de-branched and retrograded. The modified starches were then analyzed for digestibility, chain size distribution, relative crystallinity and crystallite size, thermal properties and the proportion of double helices. CAS was the most susceptible and HAS the most resistant to the action of both enzymes. Amylolysis was efficient in forming resistant starch type 3 (RS3) and high levels (> 60%) were found for all starches. RS3 content was highly correlated with the proportion of chains with degrees of polymerization between 13 and 30 for all starches, especially for the root starches, while for HAS, the high amylose content and reduction in the size of amylose chains and very long amylopectin chains also deeply contributed for the RS3 formation. These sizes (DP 13–30) are best suited for the formation of a more crystalline, more perfect, and more strongly bonded structure, composed of larger crystallites, and with a higher concentration of double helices. High correlation coefficients were found between RS3, relative crystallinity, crystallites size, and enthalpy change.
Keywords: Chain size; Crystallite size; Resistant starch; α-Amylases